Nuclear expression of a group II intron is consistent with spliceosomal intron ancestry - Chalamcharla, Venkata R. (Cold Spring Harbor Laboratory Press, 2010)
Group II introns are self-splicing RNAs found in eubacteria, archaea, and eukaryotic organelles. They are mechanistically similar to the metazoan nuclear spliceosomal introns; therefore, group II introns have been invoked as the progenitors of the eukaryotic pre-mRNA introns. However, the ability of group II introns to function outside of the bacteria-derived organelles is debatable, since they are not found in the nuclear genomes of eukaryotes. Here, we show that the Lactococcus lactis Ll.LtrB group II intron splices accurately and efficiently from different pre-mRNAs in a eukaryote, Saccharomyces cerevisiae. However, a pre-mRNA harboring a group II intron is spliced predominantly in the cytoplasm and is subject to nonsense-mediated mRNA decay (NMD), and the mature mRNA from which the group II intron is spliced is poorly translated. In contrast, a pre-mRNA bearing the Tetrahymena group I intron or the yeast spliceosomal ACT1 intron at the same location is not subject to NMD, and the mature mRNA is translated efficiently. Thus, a group II intron can splice from a nuclear transcript, but RNA instability and translation defects would have favored intron loss or evolution into protein-dependent spliceosomal introns, consistent with the bacterial group II intron ancestry hypothesis.